A rare case report of a cyclopian malformation - Priya, Shaloo; Mukherjee, Amitava; Singh, Rohit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
A rare form of median faciocerebral dysplasia, characterized by a single central orbital fossa with a tubular nose-like appendage above the orbit is known as cyclopian malformation/monster. It is the most severe form of alobar holoprosencephaly. Since most of these cases are sporadic, incompatible with life, and due to the limited literature knowledge, the exact etiology of this condition remains undetermined. However, various risk factors implicated include genetic factors and chromosomal anomalies (mostly trisomy D). Here we present a case of stillborn male cyclopian fetus born to a 34 year old 3rd gravida by caesarean section. There was no history of any drugs or alternative medicine intake (except iron-folic acid, calcium, thyroxin), radiation exposure, or a significant family history or consanguinity. Her only 33-week scan (done at a peripheral center) failed to identify any fetal abnormality. This case is reported because cyclopia is a rare/uncommon developmental anomaly especially with the advancement in antenatal ultrasonography to identify malformed fetuses early in pregnancy.